To be or not to be. Service-learning in a higher education institution - Smith-Tolken, Antoinette R.; McKay, Marianne (Bordón. Revista de Pedagogía, 2019)
INTRODUCTION. Many universities across the world prefer service learning (SL) as pedagogical framework and practice to integrate community engagement in teaching and learning. The pursuit of reciprocal collaborative relationships with society and the prominence of reflection in bridging the gap between theory and practice are characteristic of this framework. Furthermore, the focus of SL on personal growth, academic learning and social responsibility articulate well with the aim of Higher Education to develop student graduate attributes such as professionalism, critical citizenship and employment competencies. This study explores the mutations of SL in one institution where SL was articulated to be the preferred pedagogical framework for practical components of academic programmes. The question became: Is community-engaged teaching and learning a broader evolving practice of multiple pedagogical approaches in one institution or do they still constitute aspects of SL? METHOD. The study took an explorative interpretive approach to determine if SL was the only pedagogy practiced in the institution and examined the concept of collaborative engaged teaching and learning. It started with a rapid survey of all courses that was offered using experiential pedagogy and a report was compiled. In a follow-up study, specific academic programmes were purposively selected and educators were asked to analyse the approaches they were using. This was followed by purposive open-ended interviews with specific course facilitators about their teaching practice. A round table discussion was held where everyone presented his or her work. RESULTS. Content analysis showed a diversity of learning strategies. It was found that not all courses followed specific service learning methodology, but a mixture of practicums, including internships, community-based learning and work integrated learning. Multiple pedagogical approaches and methodologies were used. During interviews and presentations, it was found, however, that all courses followed at least one of the SL tenets namely service, academic learning, reflection, students developing a social responsibility and competencies. DISCUSSION. Although SL was used as a basis for their teaching/learning strategy, many of the respondents felt they did not practice SL as the latter was experienced as prescriptive and not always applicable in its entirety. Community-engaged teaching and learning (CETL) evolved as an inclusive concept that encompass multiple pedagogies that strengthen the notion of engaged teaching and engaged research as engaged scholarship. A typology of student engagement challenges the Furco (1996) depiction of SL and related activities and introduces the new concept of community-engaged teaching and learning.